FORMS AND FUNCTION OF NOUN PHRASES WITH SPECIAL REFERENCE TO CESAR MILLAN’S BOOK - Arif Gunasa, I Putu (Humanis; Volume 10. No 2. Februari 2015)
This paper is entitled “Form and Function of Noun Phrase with special reference of Cesar Millan”. The reason of choosing this topic is that noun phrase plays an important role in the construction sentence. To find out the data the data source was read carefully, then underlined them and quoted them based on the types of them. It was analyzed qualitatively based on the previous theories expressed above and the tree diagram theory was adopted from Brown and Jim Miller in their book “Syntax, 4 Linguistic Introduction to sentence to Sentence Structure (1982). The aim of this paper is to find out and identify the form of The English complex noun phrase and the tree diagram. The concept of the form of noun phrase structures in was proposed by Quirk and Greenbaum in their book entitle “A University of English Grammar (1973)”. The book was chosen after considering that there are many complex noun phrases applied in the sentences, which are needed as the data. Based on the analysis, it was found that a lot of complex noun phrases occur in the book of Cesar Millan. The form of complex noun phrases are divided into three categories, which are pre-modification noun phrase, post-modification noun phrase and multiple-modification noun phrase. Lexical and Syntactical forms of the noun phrases are descriptively analyzed in order to get a better understanding of lexical and syntactical form.
Keywords: Noun Phrase,Modified, Structure.